Mutter Krausen's Fahrt ins Glück - Jutzi, Piel (Germany, 1929)
A film about a working-class family in the late twenties in Berlin. The story of Mutter Krauses's fight for survival is conveyed in the terms that are very similar to contemporary discourse on social deprivation. The way the camera, operated by the director himself, captures scenes of everyday life in the streets of Berlin is one of the film's most memorable aspects.
Duration: 01:42:00
Keywords: Fiction films